Determinants of Payment Method Selection in E-commerce: An Empirical Analysis of Cash on Delivery (COD) Recipients at PT Pos Indonesia - Dwi Hadi Surya; Nasution, Muhammad Dharma Tuah Putra (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study investigates the factors influencing customers' decision to choose Cash on Delivery (COD) as a payment method in e-commerce transactions. Perceived Convenience, Prior Experience, and Perceived Security were identified as key factors shaping customers' preferences. The objective was to analyze the relationship between these factors and the likelihood of choosing COD. A quantitative approach using a survey methodology was employed, with a sample of 153 customers from PT. POS Indonesia. The findings reveal that Perceived Convenience significantly drives customers' decisions to select COD due to its ease and flexibility. Prior Experience also plays a crucial role, as positive past interactions build trust and reduce perceived risks, encouraging repeated use of COD. Additionally, Perceived Security emerged as a significant factor, with customers perceiving COD as a safer payment option, particularly for those concerned about online fraud.